Reformatting Grammatical Materials and Deleting Others by Scholars Selected Samples - الصُّويلِحُ, مُحَمَّدُ (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
Modern scholars believe that the ancient grammarians went too far in categorization, and subdivided the grammatical topics so that grammar became so broad that it was difficult for generations to comprehend. This is what made the Arabic grammar code - according to these modernists - shift from its essential function to the formal manifestations. Therefore, it lost its true function, which is to communicate what is going on in the speaker’s mind to the recipient. For this reason, they decided to re-format the grammatical categories, so that the future generations’ minds would not be distracted. Although modern scholars agree that Arabic grammar is difficult, they did not agree on a single solution to overcome that difficulty. Some of them advocated an alternative linguistic approach, while others called for a re-reading of the grammatical heritage in the light of modern Western theories. Some of them advocated rectification and refinement, while others demanded reviewing the grammatical heritage, especially the Kofis.